Gonadorelins adherence in prostate cancer: A time‐series analysis of England's national prescriptions during the COVID‐19 pandemic (from Jan 2019 to Oct 2020). Issue 6 (19th August 2021) - Barrett, Ravina; Barrett, Robert; Dhar, Kalyan; Birch, Brian
Abstract: Objective: To examine the effect of the COVID‐19 pandemic on gonadorelin analogue prescription for community patients in England. Materials and methods: We included data from all primary‐care patients who had relevant prescriptions dispensed in the community in England. Descriptive statistics and interrupted time series analysis over 22 months (15 months before and 7 months after lockdown) was evaluated. Results: A total of 22 months' worth of data were analyzed (or 1 041 638 total items, monthly average 47 347 items). Goserelin; leuprorelin, and triptorelin are the medicines most used by total quantity in the study period. Simple descriptive statistics show that mean values have declined during the pandemic. The Interrupted Time Series (ARIMA Modeling) shows declining trends. After the pandemic's onset, we observe a statistically significant downward trend for goserelin ( P  = .017) and leuprorelin ( P  = .014). As these are the major constituents of the model, we interpret this overall data as showing a significant downward category trend. Aside from linearity, a significant step change was noted for leuprorelin ( P  = .029) showing an increase in prescription items with a similar effect that is close to being statistically significant for goserelin ( P  = .051). The actual cost of medicines shows minimal variation suggesting that prices of individual medicines have remained stable. The regional data showed variation but this was not statistically significant. In all cases, the Oct‐20 figures are lower "year on year." This novel work reports the impact of a global pandemic on prescription volumes of prostate cancer (PCa) medicines. Conclusions: A worrying decrease in prescription medicines raises concerns for the care of PCa patients. We encourage diagnosed patients to discuss their planned care with their doctor.